GC-FID ANALYSES OF THE PHYTOCHEMICAL CONSTITUENTS OF BOILED WATER EXTRACTS OF THE LEAVES OF JUSTICIA CARNEA, FICUS CAPENSIS, MUCUNA PRURIENS AND THEIR COMBINATION - K. K. Asogwa; S. C. Udedi; I. O. Igwilo (The Bioscientist, 2024)
The decoction of the leaves of Justicia carnea, Ficus capensis and Mucuna pruriens are widely used to treat various diseases including anemia in many communities in Nigeria. In this present study, the phytochemical constituents of the boiled extracts of the leaves of Justicia carnea, Ficus capensis, Mucuna pruriens and their combination was analyzed using gas chromatography linked to flame ionization detector (GC-FID). The results obtained show that the boiled water extract of the leaf of Justicia carnea, Ficus capensis and Mucuna pruriens are rich in bioactive compounds including catechin, kaempferol, tangeretin, silymarin, Quercetin, Luteolin, Retusin, Ellagic acid, Naringenin, Isorhamnetin, Hesperidin and Epicatechin. F. capensis has the highest amount of catechin, which was the most abundance among all the phytochemicals present in the extracts. It is present at a concentration of 190.06ppm in the F. capensis extract while J. carnea, M. pruriens and their combination showed 0.57, 1.84 and 0.51ppm respectively. Sylimarin was only found in J. carnea extract while Revertrol was absence in M. pruriens extract but Present in others. These phytochemicals may be responsible for the various biological activities that has been reported on this plant leaves and their combination had a balance concentration of these phytochemicals and, thus could lead to reduce toxicity